Relationship between freshwater quality and aquatic Insects on tagal system at Sg. Moyog, Penampang, Sabah, Malaysia - Leonardo Jainih (2020)
Water is invaluable resource that increasingly being threatened and demand for more water of high quality for economic activities and domestic purposes is also increasing. Tagal in the Kadazandusun language means prohibition or forbidden from exploiting river resources by an unrelated third party and this system legally implemented since the year 2002 in Sabah. This study aimed to determine the relationship between water quality and composition as well as distribution of aquatic insect at Sg. Moyog, Sabah. Physico-chemical parameters such as pH, temperature, dissolved oxygen (DO), salinity, conductivity, total dissolved solids (TDS) were measured in this study. Ex-situ analysis such as chemical oxygen demand (COD), total suspended solids (TSS) and dissolved organic carbon (DOC) were also analyzed. At each stream, aquatic insects were sampled along approximately 100 m reach by using a kick net (mesh size 590 μm). Kampung Kibunut River (KB) was the least disturbed area compared to river in Kampung Notoruss River (NT) and Kampung Babagon River (BB) where both stations were slightly disturbed and disturbed respectively. Water quality values indicated that all parameters at Kampung Kibunut River (KB) are in Class I whereas at river in Kampung Notoruss River (NT) and Kampung Babagon River (BB), some of the parameters are categorized in Class IIA and Class IIB such as COD, nitrate and phosphate based on National Water Quality Standard for Malaysia (NWQS). A total of 18902 individuals were collected from six sampling station and 10 orders of aquatic insects were identified comprising of 39 families and 68 genera from Sg. Moyog. Trichoptera was the most abundant order with 62.62% and Cheumatopsyche spp. was the most abundant taxa (49.73%). Cluster analyses resulted in two different groups: the first group consisted of Kampung Kibunut River (KB); the second group formed by Kampung Babagon River (BB) and Kampung Notoruss River (NT). This specified that animal farms, tofu factory and recreational area from Kampung Notoruss River (NT) were grouped together with human settlements, agricultural sites and recreational area from Kampung Babagon River (BB) which varied from Kampung Kibunut River (KB) that received the least disturbance. Kruskal-Wallis test showed no significant differences between sampling locations for abundance, richness, Shannon’s diversity, Simpson’s diversity, EPT index and BMWP index. This indicated that despite receiving human disturbance and anthropogenic activities from Kampung Babagon River (BB) and Kampung Notoruss River (NT), there was no clear distinction from Kampung Kibunut River (KB). It proved that the Tagal system is an good practice that is suitable for managing the aquatic organism communities and preserving the freshwater ecosystems. Results from Canonical Correspondence analysis (CCA) indicated that most of the families from order Ephemeroptera have a strong positive association with pH, temperature and DO which indicated that Sg. Moyog has received minimal pollution as Ephemeroptera is highly sensitive to water quality degradation. The implementation of Tagal systems in Sg. Moyog is a good resource management systems and strengthening sustainable livelihoods in the communities.